Region-Specific Differences in Morphometric Features and Synaptic Colocalization of Astrocytes During Development. (21st February 2019) - Testen, Anze; Ali, Maryam; Sexton, Hannah G.; Hodges, Sierra; Dubester, Kira; Reissner, Kathryn J.; Swartzwelder, H. Scott; Risher, Mary-Louise
Graphical abstract: Highlights: There is continued, region-specific maturation of astrocytes present through adolescence and into adulthood. Cortical astrocytes continue to increase their volume and surface area into adulthood. Increased astrocyte-synapse colocalization is also observed into adulthood. Abstract: It is well established that astrocytes play pivotal roles in neuronal synapse formation and maturation as well as in the modulation of synaptic transmission. Despite their general importance for brain function, relatively little is known about the maturation of astrocytes during normal postnatal development, especially during adolescence, and how that maturation may influence astroglial–synaptic contact. The medial prefrontal cortex (mPFC) and dorsal hippocampus (dHipp) are critical for executive function, memory, and their effective integration. Further, both regions undergo significant functional changes during adolescence and early adulthood that are believed to mediate these functions. However, it is unclear the extent to which astrocytes change during these late developmental periods, nor is it clear whether their association with functional synapses shifts as adolescent and young adult maturation proceeds. Here we utilize an astrocyte-specific viral labeling approach paired with high-resolution single-cell astrocyte imaging and three-dimensional reconstruction to determine whether mPFC and dHipp astrocytes have temporally distinct maturation trajectories. mPFC astrocytes, in particular, continue to mature well into emerging adulthood (postnatal day 70). Moreover, this ongoing maturation is accompanied by a substantial increase in colocalization of astrocytes with the postsynaptic neuronal marker, PSD-95. Taken together, these data provide novel insight into region-specific astrocyte–synapse interactions in late CNS development and into adulthood, thus raising implications for the mechanism of post-adolescent development of the mPFC.